1997
DOI: 10.1021/jp970741v
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Near Ultraviolet Three Body Decay of Phosgene

Abstract: Faced with the problem of underdetermined kinetic equations in analyzing momenta and kinetic energies of three body decay fragments, we followed two conceptually different paths in order to shed light on the dynamics of the process. One is based on the evaluation of the observed kinematic quantities after introduction of physically meaningful parameters for each type of decay: sequential, synchronously concerted, and asynchronously concerted mechanism. The other one is based on an information theoretic approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…Dynamic information of two-body decay can be obtained through straightforward experiments. 3,[10][11][12][13][14][15][16][17][18][19] The mechanistic controversy for a multiplebody decay stems from the challenges of characterizing dissociation at a molecular level. 1,2 There are about 30 systems that were characterized to be capable of three-body photodissociation up to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic information of two-body decay can be obtained through straightforward experiments. 3,[10][11][12][13][14][15][16][17][18][19] The mechanistic controversy for a multiplebody decay stems from the challenges of characterizing dissociation at a molecular level. 1,2 There are about 30 systems that were characterized to be capable of three-body photodissociation up to date.…”
Section: Introductionmentioning
confidence: 99%
“…3,[10][11][12][13][14][15][16][17][18][19] The mechanistic controversy for a multiplebody decay stems from the challenges of characterizing dissociation at a molecular level. [15][16][17] A less abundant decay channel is the synchronously concerted mechanism, in which the two C-Cl bonds cleave in unison. Early studies [10][11][12] led to the proposition of a sequential decomposition mechanism via formation of the thermally instable chloroformyl ͑ClCO͒ radical with immediate subsequent decay into CO and Cl.…”
Section: Introductionmentioning
confidence: 99%
“…This is an open decay channel for all electronically excited states of H 3 . For larger molecules, three-body decay may constitute a major fragmentation pathway and has come into the focus of recent investigations [11][12][13][14]. In the case of H 3 , Peterson et al [15] found evidence for this process in dissociative charge transfer of H 1 3 in Cs, and Datz et al [16] measured the branching between two-body and three-body channels in dissociative recombination of H 1 3 with electrons.…”
mentioning
confidence: 99%
“…Carbonyl compounds are known to exhibit a complex fragmentation scheme upon irradiation by ultraviolet light because of their small threshold energy with respect to threebody decay. The decay dynamics of acetone, 1 carbonyl cyanides, 2-5 acetyl halides, 6,7 and phosgene [8][9][10] have been investigated by almost any technique offered by modern reaction dynamics, among them nonresonant and resonance enhanced photofragment translational spectroscopy, photofragment imaging, velocity-map imaging and ultrafast spectroscopy. Earlier work is compiled in a review paper about photoinduced three-body decay.…”
Section: Introductionmentioning
confidence: 99%
“…when irradiated by light at 235 nm in the peak of the first absorption band. 9 The alternative two-body channels produce a͒ Permanent address: Institute of Chemical Kinetics and Combustion, 630090 Novosibirsk, Russia.…”
Section: Introductionmentioning
confidence: 99%